2016
DOI: 10.2139/ssrn.2795968
|View full text |Cite
|
Sign up to set email alerts
|

Directed Technical Change and Economic Growth Effects of Environmental Policy

Abstract: A Schumpeterian growth model is developed to investigate how environmental policy affects economic growth when environmental policy also affects the direction of technical change. In contrast to previous models, production and pollution abatement technologies are embodied in separate intermediate good types. A set of stylized facts related to pollution emission, environmental policy, and pollution abatement expenditures is presented, and it is shown that the developed model is consistent with these stylized fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…This is demonstrated by [33], who study the location decisions of a duopolistic sector when there is the option to adopt abatement technologies. Among their main conclusions, they establish that the regulator should incentivize the adoption of these new technologies, as it reduces the incentive for relocation and has a positive effect on emissions ( [34], [35], [36]) and societal welfare. Based on these results, two fundamental points must be considered.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is demonstrated by [33], who study the location decisions of a duopolistic sector when there is the option to adopt abatement technologies. Among their main conclusions, they establish that the regulator should incentivize the adoption of these new technologies, as it reduces the incentive for relocation and has a positive effect on emissions ( [34], [35], [36]) and societal welfare. Based on these results, two fundamental points must be considered.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using panel regression analysis, Huang et al (2021) studied the factors influencing biased technical change and found that improving energy efficiency, promoting urbanization, expanding production scale, and optimizing industrial structures effectively promote biased technical change. Recently, many scholars have begun studying the impact of environmental policies on the direction of technical change (Greaker et al, 2018;Kruse-Andersen, 2016;Wang et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Figure 2. Productivity measures, Ãt , (MFP, TFP, and GDP per worker) in logs: levels and first differences,1953-2018. Source: BEA (2020a, 2020b, BLS (2020b), andFernald (2014) …”
mentioning
confidence: 99%
“…Finally, I would like to thank Mark Boroush from the National Science Foundation for providing insights and data on US R&D expenditures. The present article is a revised version of Kruse‐Andersen (2017) and Kruse‐Andersen (2018, ch. 1).…”
mentioning
confidence: 99%